Montessori Pedutology - Śliwerski, Bogusław (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
The subject of the analysis is the reception of Montessori education in post-socialist Poland. The author focuses mainly on the models of pedeutological research to emphasise the important role played by the teacher as a professional, educator, but also a human being in this alternative upbringing and education. He recalls the most important results of research on the specificity of teaching work in Montessori institutions.